Digital Transformation in Healthcare: A Bibliometric Analysis - Zhang Luxin (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study systematically examines the digital transformation in healthcare through bibliometric analysis, offering a comprehensive overview. By analyzing 918 documents, we assessed various dimensions, including geographical distribution, publication year, research domains, prolific authors, institutions, publishers, and highly cited articles. Our findings highlight the growing importance and interdisciplinary nature of this field, emphasizing the need for collaborative efforts among researchers. As digital transformation evolves, academia, industry, and policymakers must work together to leverage technological advancements to improve healthcare outcomes and enhance human well-being. Sustained and expanded research efforts are essential to fully realize its potential benefits.